Hubungan Jumlah Sel Radang Polimorfonuklear dengan Skor Alvarado pada Pasien Apendisitis Akut di RSUD Ulin Banjarmasin - Widya Wulan Fitri; Agung Ary Wibowo; Ida Yuliana Yuliana; Hery Poerwosusanta; Ika Kustiyah Oktaviyanti (Homeostasis, 2022)
Abstract: Appendicitis is the most common cause of abdominal pain in digestive surgery and requires immediate surgery to prevent complications. The diagnosis of acute appendicitis that is non-invasive, easy and fast, is using the Alvarado score and then compared with the histopathological picture of the appendix post appendicectomy. This study aims to determine the relationship between the number of polymorphonuclear inflammatory cells and the Alvarado score in acute appendicitis patients at Ulin Hospital Banjarmasin in 2016-2021. This study is an analytic observational study with a retrospective cohort approach, with a sample of 52 people who meet predetermined criteria and were selected by non-probability sampling technique. The data used for this study is the Alvarado score of acute appendicitis patients taken from secondary data and the results of the calculation of the counting of polymorphonuclear inflammatory cells in the form of primary data taken from photos of appendicitis tissue preparations of patients with appendicitis. The Pearson correlation test has shown that there is no relationship between the counting of polymorphonuclear inflammatory cells and the Alvarado score with a p value of 0.339 > 0.05 (p > 0.05). Based on the results of this study, it can be concluded that there is no relationship between the counting of polymorphonuclear inflammatory cells and the Alvarado score in acute appendicitis patients at Ulin Hospital Banjarmasin in 2016-2021. Keywords: acute appendicitis, polymorphonuclear cell (PMN) count, Alvarado score Abstrak: Apendisitis merupakan penyakit penyebab nyeri pada abdomen tersering di bidang bedah digestif dan memerlukan tindakan pembedahan segera untuk mencegah komplikasi. Diagnosis apendisitis akut yang tidak invasive, mudah dan cepat, adalah menggunakan skor Alvarado lalu dibandingkan dengan gambaran histopatologi apendiks post apendiktomi. Penelitian ini bertujuan untuk mengetahui hubungan dari jumlah sel radang polimorfonuklear dengan skor Alvarado pada pasien apendisitis akut di RSUD Ulin Banjarmasin tahun 2016-2021. Penelitian ini adalah penelitian observasional analitik dengan pendekatan kohort retrospektif, dengan jumlah sampel sebanyak 52 orang yang sesuai dengan kriteria yang telah ditentukan dan dipilih dengan teknik non probability sampling. Data yang digunakan untuk penelitian ini adalah nilai skor alvarado pasien apendisitis akut yang diambil dari data sekunder dan hasil perhitungan jumlah sel radang polimorfonuklear berupa data primer yang diambil dari foto preparat jaringan apendiks pasien apendisitis. Uji korelasi Pearson yang dilakukan telah menunjukan tidak adanya hubungan antara jumlah sel radang polimorfonuklear dan skor alvarado dengan nilai p yaitu 0,339 > 0,05 (p > 0,05). Berdasarkan hasil penelitian ini dapat disimpulkan bahwa tidak terdapat hubungan antara jumlah sel radang polimorfonuklear dengan skor Alvarado pada pasien apendisitis akut di RSUD Ulin Banjarmasin tahun 2016-2021. Kata-kata Kunci:   apendisitis akut, jumlah sel radang polimorfonuklear (PMN), skor Alvarado